Online learning from the higher education students’ point of view (Study at a Private University in Central Java Indonesia) - Yulia, Hanita; Paseleng, Mila Chrismawati (Psychology, Evaluation, and Technology in Educational Research, 2021)
Online learning conducted in some university  as a result of the COVID 19 pandemic can be said to be a fairly new learning model. It is necessary to know the students’ perception toward the online learning. Therefore, this quantitative and qualitative descriptive study aimed at describing students’ perceptions of online learning based on their experiences in participating in the online model learning and how the online learning meet their learning needs and expectations. Questionnaires given to 142 students at the Faculty of Information Technology in a private university in Central Java  were used to collect data, besides interviews and focus group discussion also employed for deeper understanding of student experiences in online learning. The results showed that there was a positive response from students towards online learning. The online learning that had been implemented could accommodate most of students’ learning needs and expectations. However, this was strongly influenced by the role of the lecturer in organizing and packaging the online learning. In addition, it required habituation and the ability of students to study independently. The existence of a learning community in online learning was also a factor that can support students’ success in participating at the online learning. Technical problems in form of equipment availability and inadequate internet access were the main obstacles in the implementation of online learning. Hopefully, the research results can be used to improve and develop an effective online learning in higher education in the future.